PEMBUATAN PROGRAM APLIKASI PEMESANAN TEMPAT & MAKANAN PADA RESTAURANT CAHAYA BARU BERBASIS WEBSITE - Ricky Sanjaya; Jap Tji Beng; Ery Dewayani (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
Restaurant Cahaya Baru  is a Restaurant which was founded in 1971 located on Jl. Tuparev No. 228 Karawang, West Java. In terms of publication, the Restaurant Cahaya Baru only uses word of mouth to disseminate information about the Restaurant Cahaya Baru. Submission of information by word of mouth is not optimal because it is limited to the scope of people's knowledge of the Cahaya Baru Restaurant. Until now, Restaurant Cahaya Baru does not have a website. The purpose of this thesis is to promote the Restaurant Cahaya Baru so that it is better known by the public, providing convenience to customers in viewing information in the form of food menus, food prices and online order so that no need to come to the restaurant. The method used for data collection is Prototyping. The programming language used is the PHP programming language and the database used is MySQL. This website can help customers make it easier to reserve places and order food online via the internet.